Pendidikan Akhlak dan Budi Pekerti Melalui Kegiatan Ekstrakurikuler: Studi Kasus Penerapan pada Peserta Didik di Madrasah Tsanawiyah Negeri 1 Manado - Arifin, Zainul; Marwiyah, Marwiyah (Tapis: Jurnal Penelitian Ilmiah, 2020)
Education is given to students not only focus on the students’ academic ability, but also on moral quality improvement. In line with the limited time of student learning, the educational institution must also be able to provide alternative additional activities to create a good moral generation, one of them with extracurricular activities. This study aimed to explain the efforts of teachers in improving the students’ morals through religious extracurricular in MTs Negeri 1 Manado and how teachers’ constraints in improving the students’ morals. This is Phenomenology Research used to identify, analyze and solve problems by using logical phenomena or reality with a qualitative approach. The results showed that daily program; those are positive behavior habits such as shalat, a weekly program such as Friday worship and tadzkir on Saturday, a monthly program such as tadzkir akbar, annual programs such as the celebration of the Prophet's Birthday, Isra 'Mi'raj, has a positive impact on students both in the school environment and family or society. These activities stand as moral guidance for students and as a tool for friendship in or out of school.